Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV MARIA S. MERIAN during cruise MSM79 - Gesine Mollenhauer; Karin A F Zonneveld (PANGAEA, 2025)
Raw bathymetry data were collected using the ship extquotesingles own Konsgberg EM122 multibeam echosounder during the RV MARIA S. MERIAN cruise MSM79/1. The cruise took place between 2018-10-29 and 2018-11-07 (EUROTHAW leg, Edinburgh, UK - Las Palmas, Spain), and between 2018-11-10 and 2018-12-03 (MACPEI leg, Las Palmas, Spain - Mindelo, Cape Verde). Bathymetric mapping was conducted along with sub-bottom profiling in the English Channel, as well as off Cape Blanc and southeast of the Cape Verde, to search for prospective core locations. Sound velocity profiles (SVP) collected during the transit and during the MACPEI leg are added to this submission. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).